NILAI-NILAI KARAKTER SEKOLAH DASAR ISLAM TERPADU NURUL FIKRI DEPOK - Fahri, Muhammad (JMIE (Journal of Madrasah Ibtidaiyah Education), 2018)
This research is aimed to describe profile of Islamic elementary education and to know the characters implemented in Nurul Fikri Integrated Islamic Elementary School. The method used is qualitative. The research found that Integrated Islamic School Network (JSIT: Jaringan Sekolah Islam Terpadu) has 11 own quality assurances implemented in their accreditation and it improves 10 Islamic characters. Beside according to JSIT quality assurance and its characters, SDIT Nurul Fikri improves character of SMART (Sholeh, Muslih, cerdAs, mandiRi and Terampil). The results of these studies can be as information, consideration and implementation for education practitioners, stakeholders, researchers and the public in general.